Change and Preservation in Language, Literature and Culture in Southeast Asia: Trends and Directions (KEMANUSIAAN The Asian Journal of Humanities, 2020)
The theme of “Change and Preservation” was developed for the Fifth International Conference on Linguistics, Literature and Culture (ICLLIC), which took place in the United Nations Educational, Scientific and Cultural Organisation (UNESCO) World Heritage Site of George Town in Pulau Pinang, Malaysia, from 29th to 30th July 2019. ICLLIC is organised by the English Language Studies Department of the School of Humanities at Universiti Sains Malaysia and was the brainchild of Shakila Abdul Manan, a former Professor of English Language Studies. She inspired and encouraged the department to organise ICLLIC, aiming to galvanise research and build networks among researchers in Malaysia and Southeast Asia. As such, ICLLIC has conventionally received strong participation from academics and postgraduate students in this region, particularly Malaysia, Indonesia, the Philippines and Thailand, even though it emphasises research in Asia as a whole. The success of the ICLLIC series throughout the years has also encouraged the English Language Studies Section to continue organising the conference.